Underweight, overweight, and weight change in older family caregivers and their care recipients: longitudinal evidence from a randomized controlled trial - Koponen, Sohvi; Nykänen, Irma; Savela, Roosa-Maria; Välimäki, Tarja; Suominen, Anna Liisa; Schwab, Ursula (Frontiers in Aging, 2024)
This study aimed to identify differences among body mass index (BMI) categories of older family caregivers (≥60 years) and their care recipients (≥65 years). Secondly, this study aimed to examine group differences and factors associated with weight change during a nutrition and oral health intervention. This secondary analysis of a randomized controlled trial (ClinicalTrial.gov (NCT04003493)) involved individually tailored nutritional guidance from a clinical nutritionist and oral health guidance from a dental hygienist. Baseline BMI differences were analyzed, followed by further analyses of group differences and associated factors of weight change over a 6-month period using generalized estimating equations. Among the participants (113 family caregivers and 107 care recipients), 36.3% and 35.1% were overweight (BMI >29 kg/m2), while 18.6% and 21.6% were underweight (BMI <24 kg/m2) at baseline, respectively. For family caregivers differences in BMI categories included age, mid-arm and calf circumferences, and plasma prealbumin concentration. For care recipients differences were observed in medication use, mid-arm and calf circumferences, Mini Nutritional Assessment scores, physical function, and number of teeth. During the 6-month intervention, there were no differences in weight change between intervention and control groups for both caregivers and care recipients. Factors significantly associated (p < 0.05) with weight loss included female sex for both caregivers and care recipients, and frailty for caregivers. Family caregivers’ characteristics were not significantly associated with weight change in their care recipients. In conclusion, being overweight is a prevalent among older family caregivers and care recipients. Factors such as age, medication use, physical function, number of teeth, and Mini Nutritional Assessment scores varied across BMI categories. Female sex was associated with weight loss in both older family caregivers and care recipients, and frailty was associated with weight loss in caregivers. However, the characteristics of family caregivers did not explain the weight loss of their care recipients.Clinical Trial Registration: [https://www.ClinicalTrial.gov/], identifier [NCT04003493].